Myoma in pregnancy and outcome after cesarean myomectomy - Valson, H.; T., Nazer; Mukergee, Sukanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of leiomyoma is 30% to70% in reproductive women. In addition to causing menstrual disorders like menorrhagia, mass in abdomen, pain and it also negatively affect fertility and pregnancy outcome. Objectives of present study was to investigate the outcome in cases of pregnancy complicated by fibroids undergoing lower segment cesarean section (LSCS) in DM WIMS Medical College and Hospital, Wayanad, Kerala, where the prevalence of fibroids is high in reproductive women. Methods: Twelve cases of leiomyoma with pregnancy underwent LSCS with myomectomy following the delivery of the baby. The indications for myomectomy during LSCS taken into consideration were firstly the size of fibroids usually less than 5 cm, mainly single myoma complicating pregnancy and sites like sub serous and intramural. The suturing of the uterus was done using polyglycolic acid of size No. 1 and polyglycolic acid suture of 2 ‘0’ for closing the dead space and with good hemostasis the operation was completed. The indications for cesarean, the average operative time for surgery, the amount of blood loss, and postoperative complications like surgical site infections were noted and outcome recorded. Results: The time taken for surgery was about 45 minutes longer, average blood loss was approximately 300 ml to 500 ml more than for a routine LSCS. There was no surgical site infections or postpartum hemorrhage in any of the cases. Conclusions: Myomectomy with caesarean in selected cases with proper indications is safe and possible in selected cases. It avoids a second surgery with its associated morbidity.